Joint optimization of primary and backup controller placement and availability link upgrade in SDN networks - Santos, Dorabella (2021)
In Software-Defined Networking (SDN), the control and data planes are decoupled, leading to a more programmable and efficient network management. In this paper, the controller placement problem in SDN is addressed, jointly with the problem of exploring a high-availability tree subgraph, in order to support delay and availability requirements between the switches and the controllers. We consider that each switch connects to a primary and to a backup controller. We formulate the joint optimization model as an integer linear programming model (ILP), and propose a heuristic method when the exact model becomes impractical. Furthermore, we compare two ILP formulations, and we also compare the controller redundancy solutions with those considering path redundancy alone.